Chapter Land use analysis and coastal structures: Adriatic Coast as a case study - Montaldi, Cristina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Coastal areas are complex and fragile nature environments, they are strongly anthropized with a high level of pollution, habitat and ecological functions loss. The study area is the Italian coastal belt between Conero Promontory and Punta Aderci. The main goal of the work is both to analyse the present mosaic of land use/cover and investigate the morphodynamic processes to define rules necessary for the sector planning (e.g., Coastal defense planning, water catchment planning) and local planning.